An intimate spectacle : dispersing the theatre : an essay presented in partial fulfillment of the degree of Master of Design, Massey University, Wellington, New Zealand - Burrell, Sarah (Massey University, 2011)
An Intimate Spectacle examines the intersection between the spectacle of the theatrical event and the subjective experience of the audience member or ‘participant’. Departing from the dynamics of spectatorship prescribed by the traditional theatre, this exploration begins to wander through the rough and surprising terrain of the city in search of an intimate form of participation. This body of work has been explored and disseminated through a series of urban workshops and performances in which a solitary participant is guided on a self-directed exploration of the city. Equipped with sound (mp3 players) and material (objects and suggestions) the individuals are invited to conduct interventions that cause them to perform a personal relationship with their urban surroundings. Participants become tourists of the everyday, dispersing traces of performance that reveal a mythic dimension in the habitual city. Theatre is typified by binary distinctions: the stage and the auditorium, the fictional and the real, the prop and the object, and the actor and the audience. As this discourse moves outside the theatre, these distinctions begin to dissolve. The roles of the actor and the audience are disestablished through the design of performances comprised solely of participants who conduct their experience through interventions and enactments.
Sound files available with hard copy
Keywords: Theatre; Spectacle; Audience; Participant; Performance; Tourism; Urban exploration